Senior high school students’ argumentation in proving mathematical induction based on mathematical abilities - Natasya Ziana Walidah; Elly Susanti (Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Argumentation and proof are two interrelated elements in mathematics, which is one of the important goals in mathematics education. Furthermore, these also need to be supported by students' mathematical abilities, so that it has implications for proving they did. This qualitative research will be explained descriptively which aims to find out senior high school students' argumentation in proving mathematical induction. This research subjects consisted of six senior high school students in Surabaya who had low, medium, and high mathematical abilities. Research data were collected through a written test about proving mathematical induction. Then, the data analysis will be carried out, including: sorting the data, presenting the data, and making conclusions. The results shows that senior high school students who have medium and high mathematical abilities can proving mathematical induction which bring up claims, evidence, and reasoning in their argumentation. Meanwhile, senior high school students who have low mathematical abilities can proving mathematical induction which only bring up claims and evidence in their argumentation.